2022
DOI: 10.1111/ajfs.12364
|View full text |Cite
|
Sign up to set email alerts
|

Can Reform of Information Disclosure by an Exchange Restrain Corporate Fraud? Evidence from China*

Abstract: This study examines the impact of information disclosure system reform (IDSR) on corporate fraud. IDSR includes the internet-based communication platforms and the introduction of assessment methods for information disclosure. The study finds that reform in the Shenzhen Stock Exchange (SZSE) reduces the probability, frequency, and severity of corporate fraud. In contrast, the reform in the Shanghai Stock Exchange (SSE) has no such effect. The negative association between the SZSE reform and corporate fraud is m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 100 publications
(187 reference statements)
0
6
0
Order By: Relevance
“…IIPs represent a significant institutional innovation in the Chinese capital market, leveraging new technologies to strengthen communication between investors and companies. Previous studies have found that IIPs have governance benefits in monitoring management (Chau et al 2023), such as enhancing investors' demand for information and subsequently improving company disclosure (Wong et al 2023), reducing the likelihood of management fraud (Wang et al 2022), and actual earnings management (Li et al 2023). However, there is limited research on the impact of investor and management interaction on the accounting conservatism of companies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…IIPs represent a significant institutional innovation in the Chinese capital market, leveraging new technologies to strengthen communication between investors and companies. Previous studies have found that IIPs have governance benefits in monitoring management (Chau et al 2023), such as enhancing investors' demand for information and subsequently improving company disclosure (Wong et al 2023), reducing the likelihood of management fraud (Wang et al 2022), and actual earnings management (Li et al 2023). However, there is limited research on the impact of investor and management interaction on the accounting conservatism of companies.…”
Section: Introductionmentioning
confidence: 99%
“…2023), reducing the likelihood of management fraud (Wang et al . 2022), and actual earnings management (Li et al . 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…XGBoost integrated learning algorithm can more effectively predict financial fraud, which is currently an excellent classification algorithm. Therefore, in order to more accurately predict the existence of fraud in enterprises, a model based on deep learning combined with SHAP to prevent financial fraud in enterprises was studied, enabling regulators to conduct regulatory early warning for listed companies, creating a good ecological environment for the healthy growth of the capital market [4][5][6]. The research proposed combining ratio scaling with XGBoost model.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, due to the development and changes of the social and economic environment, new transactions and events are constantly appearing, and the current financial reports are increasingly exposed to drawbacks and shortcomings, so they need to be constantly adjusted and improved. It can be predicted that today's financial report will change greatly in the near future [4] .…”
Section: Introductionmentioning
confidence: 99%